A semi‐implicit scheme for large Eddy simulation of piston engine flow and combustion. (26th January 2012) - Yu, R.; Bai, X. S.
SUMMARY A semi‐implicit scheme is presented for large eddy simulation of turbulent reactive flow and combustion in reciprocating piston engines. First, the governing equations in a deforming coordinate system are formulated to accommodate the moving piston. The numerical scheme is made up of a fourth‐order central difference for the diffusion terms in the transport equations and a fifth‐order weighted essentially nonoscillatory (WENO) scheme for the convective terms. A second‐ order Adams–Bashforth scheme is used for time integration. For higher density ratios, it is combined with a predictor–corrector scheme. The numerical scheme is explicit for time integration of the transport equations, except for the continuity equation which is used together with the momentum equation to determine the pressure field and velocity field by using a Poisson equation for the pressure correction field. The scheme is aimed at the simulation of low Mach number flows typically found in piston engines. An efficient multigrid method that can handle high grid aspect ratio is presented for solving the pressure correction equation. The numerical scheme is evaluated on two test engines, a laboratory four‐stroke engine with rectangular‐shaped engine geometry where detailed velocity measurements are available, and a modified truck engine with practical cylinder geometry where lean ethanol/air mixture is combusted under a homogeneous charge compression ignition (HCCI) condition. Copyright © 2012 John Wiley & Sons, Ltd.